Current strategies in the management of melasma: pathogenesis, risk factors and comprehensive treatment approaches - Walaszek, Marta; Jusiak, Justyna; Luczak, Jeremi; Sobkowiak, Maciej; Sobkowiak, Paulina; Łuczak, Janusz; Dżumaga, Justyna; Janiszewska, Michalina; Łazik, Maria; Dybowska, Roksana (Journal of Education, Health and Sport, 2026)
Melasma is an acquired pigmentary disorder characterized by symmetric hyperpigmented macules and patches on sun‑exposed facial areas. Its multifactorial pathogenesis includes melanocyte hyperactivity, dermal melanophages, vascular and inflammatory components, oxidative stress and hormonal drivers. Because of its chronic, relapsing nature and high risk of recurrence, melasma management requires individualized, multimodal approaches combining strict photoprotection, topical agents, systemic medications when indicated, and procedure‑based therapies for refractory or mixed cases. This review summarizes current knowledge of pathomechanisms and precipitating factors, evaluates therapeutic options (topical, systemic and procedural), compares modalities, and proposes practical algorithms for management and maintenance.